IMPACT OF SECOND LANGUAGE CONCEPTS ON THE IMPROVEMENT OF WRITING SKILLS - Wickramanayake, L.C.D. (My University, 2006)
Learning to write in English and teaching writing to EFL students have caused a multitude of problems both to the student and the teacher. Preliminary investigations conducted on students' difficulties in writing revealed their inability to string the words to obtain a meaningful sentence or translate their generated thoughts into correct linguistic form and their inadequacy of knowledge in grammar. Therefore, the aim was to design a teaching procedure to teach writing to EFL students, utilizing the concepts which emerged through second language research in the recent past: the comprehensible input hypothesis (Krashen, 1982,Van Pattern 1987), the comprehensible output hypothesis (Swain, 1995), scaffolding (Bruner, 1966, Wood,Bruner,Ross, 1976, Vygotsky, 1978,Gillimore, 1998),feedback,(Hyland &Hyland,2006),recycling (Mayer 1983), to find the impact the second language concepts have in improving writing in EFL students. The action research study was conducted with two samples of grade 11 students of different schools in varied scholastic backgrounds. Initially, the simple sentence patterns of English and basic sentence grammar were pre taught and each lesson conducted initially and thereafter moved through the cycle: plan, action, observation, and reflection. Then the consecutive lesson was decided by the observations of the preceding lesson. Focus on form activities which draw the learners' attention to the linguistic form while focusing on meaning of the content were based on both the comprehensible input & output hypothesis; used by matching the cognitive abilities of the students. Teaching techniques such as providing scaffolding, feedback; recycling the lessons when necessary, too were administered within the lesson. In addition, the students' self reports, audio recording, mini tests, portfolios and questionnaires were the data collection tools manipulated in this study. Analyzing data revealed that pre teaching the basic syntactic patterns of English & teaching the basic grammar, improved writing. Further, it was disclosed that the focus on form activities, scaffolding, feedback and recycling the lessons too enhanced writing. Furthermore, it showed that collaborative teaching; using LI to teach writing also had an impact on enhancing writing. Moreover, the data unveiled that a pattern emerging in writing development in the two EFL samples, which required further research with different student samples prior to a final generalization